People who move and need news: The economic and social value of providing digital journalism services for mobile and remote audiences - Cokley, John; Comrie, Margie (Journal of Telecommunications and the Digital Economy, 2013)
This article proposes historical precedents for policies which support journalism enterprises that serve populations 'on the move' using communications networks and technologies. A contemporary case study is used to support an economic argument that there is a rationale for continued governmental intervention in journalism in the sphere of the international and domestic movement of passengers, cargo and discrete groups of linked individuals. It concludes that this sphere represents a valuable productivity opportunity for Australia which the Federal Government should exploit.